Dīwān-i Hātif-i Iṣfahānī - Iṣfahānī, Hātif (Miras Maktoob, ISBN: 9789004365452., 2019)
Persian poetry of the pre-modern era is divided into three successive styles, each belonging to a different period: Khurāsānī, ʿIrāqī and Hindī. The Hindī style is called such because in Safavid times, during which it developed, poets no longer enjoyed the shah's patronage so that many of them went to India, where Persian poetry had flourished since Ghaznavid times (11th-12th century CE). The Hindī style is often regarded as a lesser style, but has the merit of having put a halt to the decline that Persian poetry was suffering from at the time and also, by its accessible language and subject matter, of having brought poetry within reach of the ordinary man. The poetry of Hātif Iṣfahānī (d. 1198/1783) published here was written in the latter half of the 12th/18th century, at the beginning of the neo-classical period of return ( bāzgasht ) to the poetical styles of the pre-Safavid era.